The Nesting Success of Taita Thrush Turdus helleri in Afrotropical Fragments, Kenya - Waweru, N.; Borghesio, L.; Muchai, M.; Waweru, C. (Africa Environmental Review Journal, 2018)
Nesting behavior and nest success are key components for assessing the conservation status of avian species. This study focused on the critically endangered Taita Thrush (Turdus helleri), endemic to the Taita Hills of southern Kenya. We surveyed all the four remnant forests fragments (Chawia, Yale, Mbololo and Ngangao) where the species survives. Taita thrush nests were placed on well branched trees with at least a climber at an average height of 4.3 m (range 2 m -7 m, N = 38) above the ground. Based on the data from the thirty eight nests found, on average, 34% of all the nests initiated survived to produce fledglings across all the four fragments. Success rates appeared to differ across forest fragments. Daily survival probability was estimated in all the four fragments and later narrowed down to two large fragments that had more than one nest. Daily survival probability for all four fragments was estimated at 0.93 ± 0.03 with a daily survival rate for egg incubation and nestling periods of 0.11. Daily survival probability for Ngangao and Mbololo was estimated at 0.88 ± 0.08 and 0.95 ± 0.06 respectively with a daily survival rate for egg incubation and nestling period(s) of 0.2 and 0.21 respectively. Continuous nest monitoring revealed that nest predation accounted 55.3% (unknown animal predators 76.19% and known animal predation 23.81%), abandoned nests 10.53% (unknown reasons for nest abandonment) and 34.20% fledged nests. The predators included, a Boomslang (Dispholidus typus) snake, a nocturnal rodent(not clearly identified by camera) and an African goshawk (Accipiter tachiro) for both stages of incubation and nestling development(snake-1 nest, bird of prey -1 nest, rodents- 3 nests and unknown predators- 16 nests). Nest predation was highest in Ngangao but this could have been attributed by the fact that the same fragment had more nests observed than all other fragments. The low nesting success of Turdus helleri suggests that conservation efforts should ensure that Taita forest fragments are properly managed to maintain natural habitat.